Sophorolipid: a glycolipid biosurfactant as a potential therapeutic agent against COVID-19. Issue 2 (20th December 2021) - Daverey, Amita; Dutta, Kasturi; Joshi, Sanket; Daverey, Achlesh
ABSTRACT: Biosurfactants are natural surfactants produced by a variety of microorganisms. In recent years, biosurfactants have garnered a lot of interest due to their biomedical and pharmaceutical applications. Sophorolipids are glycolipid types of biosurfactants produced by selected nonpathogenic yeasts. In addition to the detergent activity (reduction in surface and interfacial tension), which is commonly utilized by biomedical applications, sophorolipids have shown some unique properties such as, antiviral activity against enveloped viruses, immunomodulation, and anticancer activity. Considering their antiviral activity, the potential of sophorolipids as an antiviral therapy for the treatment of COVID-19 is discussed in this review. Being a surfactant molecule, sophorolipid could solubilize the lipid envelope of SARS-CoV-2 and inactivate it. As an immunomodulator, sophorolipid could attenuate the cytokine storm caused by the SARS-CoV-2 upon infection, and inhibit the progression of COVID-19 in patients. Sophorolipids could also be used as an effective treatment strategy for COVID-19 patients suffering from cancer. However, there is limited research on the use of sophorolipid as a therapeutic agent for the treatment of cancer and viral diseases, and to modulate the immune response. Nevertheless, the multitasking capabilities of sophorolipids make them potential therapeutic candidates for the bench-to-bedside research for the treatment of COVID-19.